FRAM—The Robotic Telescope for the Monitoring of the Wavelength Dependence of the Extinction: Description of Hardware, Data Analysis, and Results. (19th January 2010) - Prouza, Michael; Jelínek, Martin; Kubánek, Petr; Ebr, Jan; Trávníček, Petr; Šmída, Radomír
Abstract : FRAM—F/(Ph)otometric Robotic Atmospheric Monitor is one of the atmospheric monitoring instruments at the Pierre Auger Observatory in Argentina. FRAM is an optical telescope equipped with CCD cameras and photometer, and it automatically observes a set of selected standard stars. Primarily, FRAM observations are used to obtain the wavelength dependence of the light extinction. FRAM telescope is also able to observe secondary astronomical targets, and namely the detection of optical counterparts of gamma-ray bursts has already proven to be successful. Finally, a wide-field CCD camera of FRAM can be used for rapid monitoring of atmospheric conditions along the track of particularly interesting cosmic ray showers. The hardware setup of the telescope, its software system, data taking procedures, and results of analysis are described in this paper.